2019
DOI: 10.1177/0961203319860579
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of serious infections over time in systemic lupus erythematosus patients: data from a multi-ethnic, multi-national, Latin American lupus cohort

Abstract: Aim The aim of this study was to identify factors predictive of serious infections over time in patients with systemic lupus erythematosus (SLE). Methods A multi-ethnic, multi-national Latin American SLE cohort was studied. Serious infection was defined as one that required hospitalization, occurred during a hospitalization or led to death. Potential predictors included were sociodemographic factors, clinical manifestations (per organ involved, lymphopenia and leukopenia, independently) and previous infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
3
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 44 publications
4
65
3
7
Order By: Relevance
“…However, our result con rmed that renal involvement is signi cantly associated with active infection in the multivariate GEE analysis, in consistent to previous study [40]. Of note, our data is in consistent with Pimentel et al that any increase in the SDI was associated with the occurrence of serious infections [39]. We also showed that compared to PCT, CRP is a more sensitive and speci c marker for diagnosing bacterial infections in SLE [41].…”
Section: Parameters Predictive Of Acute Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, our result con rmed that renal involvement is signi cantly associated with active infection in the multivariate GEE analysis, in consistent to previous study [40]. Of note, our data is in consistent with Pimentel et al that any increase in the SDI was associated with the occurrence of serious infections [39]. We also showed that compared to PCT, CRP is a more sensitive and speci c marker for diagnosing bacterial infections in SLE [41].…”
Section: Parameters Predictive Of Acute Infectionsupporting
confidence: 93%
“…Multivariate GEE analysis showed that SDI score, fever temperature, CRP level, PCT levels, lymphocyte percentage, NLR, Hb levels, and SLEDAI 2K renal score are independent parameters for predicting acute infection in SLE patients (Table 3b). Renal disease, despite being associated with infections in the univariate analysis, has not retained the statistical signi cance in the multivariate analysis in some series [38,39]. However, our result con rmed that renal involvement is signi cantly associated with active infection in the multivariate GEE analysis, in consistent to previous study [40].…”
Section: Parameters Predictive Of Acute Infectionsupporting
confidence: 85%
See 1 more Smart Citation
“…Conducted primarily in the context of rheumatoid arthritis, studies examining tapering or discontinuation of biologics or JAK inhibitors suggest that a large proportion of patients experience rheumatic disease flare (78)(79)(80)(81). This is relevant because underlying inflammation or disease activity has been implicated as a risk factor for infection (82,83), a risk that may be heightened further in the context of "rescue" glucocorticoids. Although biologic therapies are associated with an increased risk of hospitalization due to serious infection, at least one report in rheumatoid arthritis has suggested that they are associated with a reduced risk of sepsis or fatal outcome, as compared to nonbiologic DMARDs, among patients developing serious infection with these therapies (84).…”
Section: Rheumatic Disease Treatments Ace Inhibitors Andmentioning
confidence: 99%
“…In this record-linkage study, however, no effort was made to adjust the results for confounding by indication. This approach is necessary because glucocorticoid doses are linked to clinical activity, and increased disease activity is associated with an increased risk of infections in several rheumatic diseases [142][143][144][145][146][147] .…”
Section: Disease and Treatment Complicationsmentioning
confidence: 99%